Persepsi Wisatawan terhadap Sapta Pesona Objek Wisata Sejarah Istana Siak Assherayah Hasyimiah Provinsi Riau - Tia Pangestika; Dasrizal Dasrizal; Rika Despica (Journal on Education, 2024)
This research aims to determine 1) tourists' perceptions regarding the historical tourist attraction of the Siak Assherayah Palace, Riau Province, 2) the implementation of the sapta charm carried out by managers at the historical tourist attraction of the Siak Assherayah Hasyimiah Palace, Riau Province. This type of research is Quantitative Descriptive using Accidental Sampling, a data collection technique that describes observations and documentation of research results in the field and tourists' perceptions of the historical tourist attraction Siak Assherayah Hasyimiah Palace, Riau Province.The research results are: 1) Tourists' perceptions of Sapta Pesona consisting of something to see, something to do, and something to buy at the Siak Palace tourist attraction produce an average score of "interesting". So it proves that all 3 indicators of Sapta Pesona have a relatively attractive value for tourists' perception. 2) The implementation of Sapta Pesona by the management of the Siak Palace tourist attraction can be carried out "very well". This can be seen by the involvement of all managers and parties concerned in developing the tourist attraction directly in the implementation of the 7 Sapta Pesona indicators which consist of safe, orderly, clean, cool, beautiful, friendly, and a memorable tourist attraction of the Siak Palace.